1993
DOI: 10.1016/0014-5793(93)80838-l
|View full text |Cite
|
Sign up to set email alerts
|

Truncated GroEL monomer has the ability to promote folding of rhodanese without GroES and ATP

Abstract: Similar to chaperonins from other sources, intact chaperonin from Escherichia coli (GroEL) exists as a tetradecamer, and the ability to promote folding of other proteins has been considered to be dependent on this oligomeric structure. However, the peptide fragments of GroEL of molecular size 34-50 kDa, which are produced by limited proteolysis of monomeric GroEL and are unable to assemble into an oligomer, retain the ability to promote folding of rhodanese even though the yield of productive folding is lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…In addition, it has been observed that folding of hen lysozyme can be promoted by GroEL alone, in the absence of GroES and ATP (20). Similar results have been demonstrated for barnase (21) and for rhodanese (22).…”
supporting
confidence: 88%
“…In addition, it has been observed that folding of hen lysozyme can be promoted by GroEL alone, in the absence of GroES and ATP (20). Similar results have been demonstrated for barnase (21) and for rhodanese (22).…”
supporting
confidence: 88%
“…One model of GroEL action [39] assumes the possibility of interaction of free monomers with non-folded proteins, followed by the formation of the 7-mers and 14-mers. A chaperone activity of GroEL monomers different from that of the 14-mers has recently been discovered [41]. It is a question for future studies whether the dynamic Mg-ATP-dependent transitions between the monomeric and 14-meric forms can play a particular role in the functioning of the chaperonins.…”
Section: Mg-atp (Adp)mentioning
confidence: 99%
“…The protein GroEL was purified by modifications of the procedure included in Ref. 13. After ammonium sulfate fractionation, the protein was purified by means of three chromatographic steps: DEAE-Sephacel, gel filtration through Sepharose CL-4B, and affinity chromatography through red agarose (14).…”
Section: Methodsmentioning
confidence: 99%